Analysis Method of Lactoferrin Based on Uncoated Capillary Electrophoresis. Issue 3 (26th July 2021) - Chen, Hui; Wang, Zhenyu; Fan, Fengjiao; Shi, Pujie; Xu, Xianbing; Du, Ming; Wang, Cong
Abstract : The analysis of lactoferrin separation will be an important application in prospect. To develop a new strategy for the detection of lactoferrin, this work adopted the method of uncoated Capillary Electrophoresis (CE), through optimizing the parameters of background electrolyte, pH, surfactant, buffers of the system solution. The optimum lactoferrin separation by CE is 50 mM phosphates buffer added 6M urea. In positive voltage, lactoferrin was separated by CE at pH 4.0. In reverse voltage, lactoferrin can also be separated at pH 10.0 with 50 mM ammonium ace. The auxiliary air pressure was got involved to decrease the absorption by silica capillary through a range of gradient intensity of air pressure. By comparison with 1.2, 1.5 and 1.8 psi, the pressure of 0.5 psi can significantly alleviate the absorption. The best detection conditions of lactoferrin were obtained, which are pH 4.0, 50 mM phosphates with 6M urea, 0.5 psi auxiliary air pressure with the limit of quantification at 0.04 mg/mL and the limit of detection at 0.01 mg/mL. Finally, lactoferrin can be quantitatively detected well and effectively, which the standard curve is y = 117807 x + 3018.61374. GRAPHICAL ABSTRACT: